Vocational high school students mathematical problem-solving skills in PBL on composite functions - Dhiantika Aulia Hasna; Dwi Astuti (Universitas Ahmad Dahlan, 2026)
Mathematical problem-solving skills remains a critical concern in Indonesian education. PISA 2022 results showing that Indonesian students’ mathematical performance is significantly below the OECD average. This issue is particularly important in vocational high schools, where mathematics is closely related to technical and workplace applications. Although Problem Based Learning (PBL) has been widely reported as effective in improving students’ problem-solving skills, most previous studies were conducted in general senior high schools and primarily focused on learning outcomes rather than examining students’ problem-solving processes in depth. Research specifically analyzing vocational students’ problem-solving characteristics at each stage of Polya’s framework within PBL, particularly on composite functions, remains limited. This study aims to fill this gap by qualitatively analyzing Grade XI vocational students’ mathematical problem-solving characteristics at each stage of Polya’s framework within PBL instruction on composite functions. A qualitative descriptive approach was employed involving 34 students. Data were collected through validated essay tests, observations, and interviews. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The findings indicate that most students were categorized at a moderate level (83.33%), demonstrating adequate procedural ability but weaknesses in the planning and reflection stages. The study highlights an imbalance between procedural and metacognitive development and suggests the need for explicit scaffolding in planning and reflection to strengthen vocational students’ systematic problem-solving skills.